Metode Penyaringan Ekstrak Daun Kelor (Moringa oleifera) sebagai Pupuk Organik Cair bagi Pertumbuhan dan Hasil Tanaman Sawi (Brassica juncea, L) - Mohamad Ihsan; Srie Juli Rachmawati; Irsan Styadi (Daun: Jurnal Ilmiah Pertanian dan Kehutanan, 2020)
The use of liquid organic fertilizers is currently increasing. This study aims to determine the effect of the moringa leaf extract filtering method (Moringa oleifera, Lam) as a liquid organic fertilizer for growth and yield of mustard greens (Brassica juncea, L) and to determine the response of plant to the concentration of liquid organic fertilizer. The research design used was a two-factor factorial randomized completely block design with three replications. The first factor treatment was the type of moringa leaf extract filtering method (filtered with cloth, filtered with ordinary filter paper, and filtered with Whatman filter paper). The second factor was the concentration of organic liquid fertilizer from moringa leaf extract (0%, 5%, 10%, 15%). The data were analyzed with variance at the 5% and 1% significant levels, and were further tested using Duncan's Multiple Range Test (DMRT) at the 5% significant level. The results showed that the filtering method of moringa leaf extract had an effect on mustard greens for the parameters of plant height, leaf width, fresh plant weight, consumption of mustard greens per plant, and weight of consumption of mustard greens per plot. The filtering treatment of moringa leaf extract using ordinary filter paper gave the best results, with the best concentration of extracts was 5%.